Active recovery of the finger flexors enhances intermittent handgrip performance in rock climbers. Issue 7 (2nd October 2016) - Baláš, Jiří; Michailov, Michail; Giles, David; Kodejška, Jan; Panáčková, Michaela; Fryer, Simon
Abstract: This study aimed to (1) evaluate the effect of hand shaking during recovery phases of intermittent testing on the time–force characteristics of performance and muscle oxygenation, and (2) assess inter-individual variability in the time to achieve the target force during intermittent testing in rock climbers. Twenty-two participants undertook three finger flexor endurance tests at 60% of their maximal voluntary contraction until failure. Performances of a sustained contraction and two intermittent contractions, each with different recovery strategies, were analysed by time–force parameters and near-infrared spectroscopy. Recovery with shaking of the forearm beside the body led to a significantly greater intermittent test time (↑ 22%, P  < .05), force–time integral (↑ 28%, P  < .05) and faster muscle re-oxygenation (↑ 32%, P  < .05), when compared to the hand over hold condition. Further, the ratio of intermittent to continuous test time distinguished specific aerobic muscular adaptations among sport climbers (2.02), boulderers (1.74) and lower grade climbers (1.25). Lower grade climbers and boulderers produced shorter duration contractions due to the slower development of target force during the intermittent test, indicating worse kinaesthetic differentiation. Both the type of recovery and climbing discipline determined muscle re-oxygenation and intermittent performance in rock climbers.